Matematické metody v ekonomii - Válka, Vojtěch (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Tato bakalářská práce zpracovává problematiku obyčejných diferenciálních rovnic prvního řádu. První část je věnována teorii diferenciálních rovnic. Ve druhé části jsou uvedeny řešené i neřešené příklady na jednotlivé druhy diferenciálních rovnic. Na závěr je uvedeno několik příkladů použití diferenciálních rovnic v ekonomii. Práce má sloužit jako učební materiál pro studenty ekonomických oborů.

This thesis is focused on problems of ordinary differential equations of the first degree. The first part is dedicated to theory of differential equations. In the second part, solved and unsolved examples of individual types of differential equations are presented. In closing, there are few examples of economic applications. The thesis serve as a study material for students of economic faculty.
Mathematical Methods in Economics
Keywords: Obyčejné diferenciální rovnice; soustavy diferenciálních rovnic; sbírka úloh; aplikace.; Ordinary differential equations; systems of differential equations; collection of exercises; applications.